2020
DOI: 10.1088/1741-2552/ab937f
|View full text |Cite
|
Sign up to set email alerts
|

Beta-band power modulation in the human hippocampus during a reaching task

Abstract: Objective.-Characterize the role of the beta-band (13-30 Hz) in the human hippocampus during the execution of voluntary movement.Approach.-We recorded electrophysiological activity in human hippocampus during a reach task using stereotactic electroencephalography (SEEG). SEEG has previously been utilized to study the theta band (3-8 Hz) in conflict processing and spatial navigation, but most studies of hippocampal activity during movement have used noninvasive measures such as fMRI. We analyzed modulation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Previous studies from our group utilized stereotactic electroencephalography (SEEG) to characterize the relationship between the hippocampal beta band and motor output. Like prior non-hippocampal motor studies [17,18], we found decreases in hippocampal beta band power during the motor response phase compared with the fixation phase in a simple reaching task [19]. In a separate study, we examined beta power in the hippocampus during a Go/No-Go (GNG) task.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Previous studies from our group utilized stereotactic electroencephalography (SEEG) to characterize the relationship between the hippocampal beta band and motor output. Like prior non-hippocampal motor studies [17,18], we found decreases in hippocampal beta band power during the motor response phase compared with the fixation phase in a simple reaching task [19]. In a separate study, we examined beta power in the hippocampus during a Go/No-Go (GNG) task.…”
Section: Introductionsupporting
confidence: 55%
“…Beta activity during the response phase of a GNG task signifies reactive motor inhibition (in response to the GNG cue) [19,20]. On the other hand, beta activity before the response phase of a GNG task (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The beta band has been well studied throughout the motor system where it has been observed in the motor cortex, pre-motor cortex, basal ganglia, cerebellum, peripheral nervous system, and hippocampus [41,50,51], typically with a significant decrease in power during voluntary movements [42,51,67,68]. Conversely, in pathologic neurologic and motor conditions such as Parkinson's disease, motor system inhibition is associated with an increase in the betaband power [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The beta-band frequency has been the subject of multiple investigations in motor [41][42][43][44][45][46] and attentional control [47][48][49]. In the motor cortex, pre-motor cortex, basal ganglia, cerebellum, peripheral nervous system, and hippocampus [41,50,51], significant decreases in beta-band power have been observed during voluntary movement. In addition to its role in the motor system, the beta band has been widely studied in attentional control.…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed PAC changes between baseline and cue presentation in stimulus-locked segments (200-800 ms after cue onset [2,44]) in both congruent and incongruent conditions for each patient. We found that five out of eight patients (the identical patients who showed significant increased theta-LG PAC values from baseline in the OFC during successful trials of the incongruent condition) showed increased theta-LG PAC values from baseline in the OFC during successful trials of the incongruent condition (cluster-based permutation t-test, p < 0.05).…”
Section: Theta-lg Pac Increasesmentioning
confidence: 99%